Efektifitas Spiritual Emotional Freedom Technique (SEFT) dan menyanyi terhadap tekanan darah lansia di rumpelsos pucang gading semarang - Sonhaji Sonhaji; Roland Lekatompessy (Health Sciences and Pharmacy Journal, 2019)
The result of statistical analysis obtained data on the average blood pressure inthe left group before being given the intervention of 173,76/96,41 while after being given the intervention of 170,29/93,82. On the singing group before being given intervention, the average of blood pressure of 153,06/87,41 and after being given intervention tobe 168/87. Camparative test results in both groups between before and after ihe invention were obtained p – value = 0,00 (p- value p 0,05). Conclusion was spiritual emotional freedom techneque (SEFT) is more effective than singing to reduce the blood pressurenof the elderly with hypertension in social service home, Pucang Gading, Semarang. One of the body system disorders that is often experienced by the elderly. Namely the cardiovascular system such as hypertension. Hypertension of elderly can caused bad condition such as heartdiscase, stroke and kidney failure, there fore, intervention is needed to maintain blood pressure within normal himits.